EFFECT OF DELAY TIME IN URINE EXAMINATION ON ALCOHOL CONCENTRATION - Dabi, Aberina; Prihatiningsih, Diah; Sudarma, Nyoman (PT. Jurnal Center Indonesia Publisher, 2025)
Urine alcohol testing plays a vital role in detecting alcohol consumption for clinical and forensic purposes, yet its results may be influenced by pre-analytical factors such as the delay between sample collection and laboratory analysis. This study aimed to evaluate the effect of delay time before urine examination on alcohol concentration. An experimental One-Shot Case Study design was conducted involving 44 participants in Denpasar who had consumed alcohol. Alcohol concentration was measured immediately, after a 2-hour delay, and after a 4-hour delay using the Alcohol Urine Rapid Test Dipstick Allchek, and the data were analyzed using the Kruskal-Wallis test. The findings showed that average urine alcohol levels increased numerically after a 2- and 4-hour delay compared to immediate testing; however, this change was not statistically significant (p=0.131). These results confirm that delaying urine alcohol examination up to 4 hours does not significantly alter detectable alcohol concentrations, although prompt testing is still recommended to ensure result accuracy and minimize the risk of false positives. This study provides important insights for the development of standard operating procedures regarding urine alcohol analysis in laboratory practice.